Interaction of carbohydrate binding module 20 with starch substrates. Issue 43 (9th August 2019) - Ngo, Son Tung; Tran-Le, Phuong Duy; Ho, Giap T.; Le, Loan Q.; Bui, Le Minh; Vu, Bao Khanh; Thu Phung, Huong Thi; Nguyen, Hoang-Dung; Vo, Thanh-Sang; Vu, Van V.
Abstract : CBM20 quickly disrupts small helical amylose substrates and exhibits optimal binding affinity when the substrate has three or more parallel double helices. Abstract : CBM20s are starch-binding domains found in many amylolytic enzymes, including glucoamylase, alpha-amylase, beta-amylases, and a new family of starch-active polysaccharide monooxygenases (AA13 PMOs). Previous studies of CBM20–substrate interaction only concerned relatively small or soluble amylose molecules, while amylolytic enzymes often work on extended chains of insoluble starch molecules. In this study, we utilized molecular simulation techniques to gain further insights into the interaction of CBM20 with substrates of various sizes via its two separate binding sites, termed asBdS1 andBdS2 . Results show that substrate binding atBdS1 involving two conserved tryptophan residues is about 2–4 kcal mol −1 stronger than that atBdS2 . CBM20 exhibits about two-fold higher affinity for helical substrates than for the amylose random coils. The affinity for amylose individual double helices does not depend on the helices' length. At least three parallel double helices are required for optimal binding. The binding affinity for a substrate containing 3 or more double helices is ∼−15 kcal mol −1, which is 2–3 kcal mol −1 larger than that for individual double helices. 100 ns molecular dynamics simulations were carried out for the binding of CBM20 to an extended substrate containing 3 layers of 9 60-unit double helices (A3L). A stable conformation of CBM20–A3L was found atBdS1 . However, when CBM20 binds A3L via BdS2, it moves across the surface of the substrate and does not form a stable complex. MD simulations show that small amylose helices are quickly disrupted upon binding to CBM20. Our results provide some important molecular insights into the interactions of CBM20 with starch substrates, which will serve as the basis for further studies of CBM20-containing enzymes, including AA13 PMOs.